The Global Statistical Response of the Outer Radiation Belt During Geomagnetic Storms. Issue 9 (5th May 2018) - Murphy, K. R.; Watt, C. E. J.; Mann, I. R.; Jonathan Rae, I.; Sibeck, D. G.; Boyd, A. J.; Forsyth, C. F.; Turner, D. L.; Claudepierre, S. G.; Baker, D. N.; Spence, H. E.; Reeves, G. D.; et al.
Abstract: Using the total radiation belt electron content calculated from Van Allen Probe phase space density, the time‐dependent and global response of the outer radiation belt during storms is statistically studied. Using phase space density reduces the impacts of adiabatic changes in the main phase, allowing a separation of adiabatic and nonadiabatic effects and revealing a clear modality and repeatable sequence of events in storm time radiation belt electron dynamics. This sequence exhibits an important first adiabatic invariant ( μ )‐dependent behavior in the seed (150 MeV/G), relativistic (1, 000 MeV/G), and ultrarelativistic (4, 000 MeV/G) populations. The outer radiation belt statistically shows an initial phase dominated by loss followed by a second phase of rapid acceleration, while the seed population shows little loss and immediate enhancement. The time sequence of the transition to the acceleration is also strongly μ dependent and occurs at low μ first, appearing to be repeatable from storm to storm. Plain Language Summary: The Earth's outer radiation belt is a region of near‐Earth space composed of highly energetic electrons. Typically, the outer radiation belt is in a quiet state; however, during geomagnetic storms the outer radiation belt becomes extremely dynamic. During these storms rapid changes in the number of energetic electrons in the outer radiation belt can lead to satellite failures. Our new research has found a level repeatability in storm time outer radiation belt dynamics not previously appreciated and offers important insights into radiation belt modeling and forecasting. This new work can be used to mitigate the negative effects radiation belt electrons can have on satellite infrastructure. Key Points: Statistical assessment of the global and repeatable response of the outer radiation belt to storms Using radiation belt content derived from phase space density reduces impacts from adiabatic changes revealing a clear sequence of events The statistical response is characterized by a fast genuine‐loss dominated phase followed by a clear acceleration phase